The Economics of Health Professional Education and Careers : Insights from a Literature Review - McPake, Barbara; Squires, Allison; Mahat, Agya; Araujo, Edson C. (Washington, DC: World Bank, 2015)
The formation of health professionals is critical for the health system to function and achieve its universal health coverage (UHC) goals. This is well recognized by the majority of governments that plan for the training and regulations necessary to ensure quality. But the importance of market forces is often overlooked, resulting in interventions and regulations that often fail to achieve their intended effects. The Economics of Health Professional Education and Careers aims to inform the design of health professionals’ education policies to better manage health labor market forces toward UHC. It documents what is known about the influence of market forces on the health professional formation process. The contexts of the market for health professional training have been subject to important changes in recent decades, in particular: the growing extent of employment of mid-level cadres of health professionals; changes in technology and the associated growth of high-skilled occupations; the increasing interconnectedness of national health systems through globalization, with its implications for international health professional mobility; and the greater complexity of the public-private mix in employment options.